Du préciput au partage égalitaire - Fabienne Wateau (Mélanges de la Casa de Velázquez, 2006)
In Portugal at the end of the 19th century, hitherto indivisible landed estates (entailed) were forced to adjust to new requirements of equal sharing. The entry into force of this legislation (1867) introduced the sharing of estates among siblings, both male and female, and a complete reorganisation of the management of estates and of the place of first cousins in the family. Water rights linked to land, hitherto devolving on the eldest male heir, were thereafter distributed and shared among all the children. On the basis of an example of inheritance of goods over fourteen generations, through two systems of devolution from one to the next –primogeniture and equal sharing– the article seeks to show how and why water rights have come to be in female hands in north-west Portugal today.